Improvement of the safety of multi-floor housing - Tkachenko, T.; Mileikovskyi, V.; Dziubenko, V.; Tkachenko, O. (IOP Publishing, 2020)
To improve the safety in common areas of multi-storey buildings (lift halls, common corridors), it is proposed to renovate interiors of the areas. Such areas usually have no permanent ventilation. Thus, they can accumulate pathogenic microorganisms and viruses. The effective solution for reducing the danger is phytoncides plants. For successful phytodesign, an assortment of phytoncides plants of 11 species has been developed: Aspidistra elatior, Aglaonema “Silver queen”, Aglaonema “Maria”, Chlorophytum comosum, Chlorophytum capense, Dracena marginata, Monstera deliciosa, Philodendron scandens, Sansevieria triaeffieria trichelifera, Zamiaculcas zamiifolia. The offered assortment completely corresponds to climatic features of premises. For the normal growth and development of plants in the absence of natural light, three options for additional effective illumination are proposed.
https://doi.org/10.1088/1757-899X/907/1/012064
Keywords: green construction; multi-floor housing; indoor plant; air purification; phytodesign